Performance of fiber reinforced asphalt concrete under environmental temperature and water effects - Xu, Q.; Chen, H.; Prozzi, J.A.
This paper studies the reinforcing effects and mechanisms of fibers for asphalt concrete (AC)mixtures under the environment temperature and water effects. Four typical fiber types - polyester, polyacrylonitrile, lignin and asbestos - are studied. Laboratory tests were conduct on the fiber reinforced AC (FRAC)to measure its strength, strain and fatigue behavior. Results show that fibers have significantly improved AC's rutting resistance, fatigue life, and toughness. The flexural strength and ultimate flexural strain, and the split indirect tensile strength (SITS)at low temperature have also improved. The polymer fibers (polyester and polyacrylonitrile)have improved rutting resistance, fatigue life, and SITS more significantly than lignin and asbestos fibers, which may be primarily due to their greater networking function; while lignin and asbestos fibers result in greater flexural strength and ultimate flexural strain, which may be primarily due to their greater asphalt stabilization effect. However, fiber's effect under the water freezing- thaw effect does not seem promising, and the SITS of FRAC with lignin and asbestos fibers even reduces to some extent under this effect. It is also found that a fiber content of 0.35
Keywords: ASPHALT CONCRETE; FABRICS; MECHANICAL PROPERTY; TEMPERATURE; WATER EFFECT